Conditions of Work Motivation and Teacher Performance at Madrasah Tsanawiyah in North Sumatra - Naila Amna; Yuda Syahputra (JPP (Jurnal Pendidikan dan Pembelajaran))
This study aims to describe the conditions of work motivation and teacher performance in terms of culture in North Sumatra. This research is a quantitative descriptive research on educators in North Sumatra. The sample in this study amounted to 81 teachers (male = 29.6%; female = 70.4%) consisting of various cultures, namely: Javanese = 32.1%; Malay = 13.6%; Batak = 38.3%; Sundanese = 11.1%; and Betawi = 4.9%. Data were collected through two instruments, including the work motivation instrument, which consisted of 12 items and the employee performance instrument (the employee here is a teacher) which consisted of 12 items. Data were analyzed using JASP software analysis with descriptive techniques. The results show that Sundanese ethnicity is the highest in showing good performance compared to other ethnic groups. While the highest work motivation comes from ethnic Malay and Sundanese, meaning that teachers from ethnic Malay and Sundanese have higher work motivation than Javanese, Batak, and Betawi.